2013
DOI: 10.1007/s11199-013-0336-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender Traits and Cognitive Appraisal in Young Adults: The Mediating Role of Locus of Control

Abstract: The present study examined the relationships between masculine and feminine traits, measured using the Bem Sex-Role Inventory (BSRI), and the way young adults appraise events (i.e., as threats or as challenges). We hypothesized that the locus of control (LOC)—i.e., individuals’ perceived control over the events that affect them—mediated these relationships. We tested these assumptions on two student samples from the French-speaking part of Switzerland (N =123 and N =504). Regression analyses demonstrated that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 63 publications
(81 reference statements)
4
18
0
Order By: Relevance
“…Locus of control has been associated with stress experience (Zotovic, 2004;Sarrasin. Mayor & Faniko, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Locus of control has been associated with stress experience (Zotovic, 2004;Sarrasin. Mayor & Faniko, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic factors include age (Monteiro, Bolagun, & Oratile, 2014), gender (Chen, Wong, Ran & Gilson, 2009;Dughters, Gorka, Matuslewicz & Anderson, 2013).) and locus of control (Sarrasin, Mayor & Faniko, 2014;Lecic-Tosevski, Vukovic & Stepanovic (2011). The extrinsic factors may include level of study (Alzahem, Van der Molen, & De Boer, 2013), course of study (Nakalema & Senyonga, 2013;Gokul & Jayalakshmi, 2016) among others.…”
Section: Background To the Studymentioning
confidence: 99%
“…Our results also revealed that women reported lower threat and harm appraisals than did men. This is somewhat surprising because although only a small number of studies have examined the relationship between gender and cognitive appraisals (Eaton & Bradley, 2008;Ptacek, Smith, & Zanas, 1992;Sarrasin, Mayor, & Faniko, 2014), these studies indicate that women are more likely to report greater levels of stress and are more likely to appraise events as threatening and less challenging than men. One possible explanation for our finding that women reported less threat and harm than men may be explained through considering gender role expectations rather than just biological gender.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Traditionally, femininity is higher in women than in men and masculinity is higher in men than in women. Research shows that femininity is related to higher threat appraisal (resources assessed as lacking to face the stressor) and masculinity to higher challenge appraisal (resources assessed as sufficient to face the stressor) [32]. For this reason, notably, men are less affected by social-evaluative threat [23].…”
Section: Discussionmentioning
confidence: 99%